Characterization of two bacteriocins produced by Pediococcus acidilactici isolated from "Alheira", a fermented sausage traditionally produced in Portugal - Albano, Helena (2010)
Lactic acid bacteria were isolated from “Alheira” sausages that have been sampled from different regions in Portugal. The sausages were produced according to different recipes and with traditional starter cultures. Two isolates (HA-6111-2 and HA-5692-3) from different sausages were identified as strains of Pediococcus acidilactici. Each strain produces a bacteriocin, designated as bacHA-6111-2 and bacHA-5692-3. Both bacteriocins are produced at low levels after 18 h of growth in MRS broth (3200 AU/ml against Enterococcus faecium HKLHS and 1600 AU/ml against Listeria innocua N27). BacHA-6111-2 and bacHA-5692-3 are between 3.5 kDa and 6.5 kDa in size, as determined by tricine-SDS-PAGE. Complete inactivation or significant reduction in antimicrobial activity was observed after treatment of cell-free supernatants with proteinase K, pronase and trypsin. No change in activity was recorded when treated with catalase. Both bacteriocins are sensitive to treatment with Triton X-114 and Triton X-100, but resistant to Tween 20, Tween 80, SDS, Oxbile, NaCl, urea and EDTA. The bacteriocins remained stable after 2 h at pH 6.0. A decrease in antibacterial activity was recorded after 60 min at 100 °C. After 60 min at 80 °C, 60 °C and 25 °C the antibacterial activity against L. innocua N27 decreased by 25%. Addition of bacHA-6111-2 and bacHA-5692-3 (1600 AU/ml) to a mid-log (5-h-old) culture of L. innocua N27 inhibited growth for 7 h. Addition of the bacteriocins (3200 AU/ml) to a mid-log (5-h-old) culture of E. faecium HKLHS repressed cell growth. The bacteriocins did not adhere to the surface of the producer cells. Both strains contain a 1044 bp DNA fragment corresponding in size to that recorded for pediocin PA-1. Sequencing of the fragments from both bacteriocins revealed homology to large sections of pedA (188 bp), pedB (338 bp) and pedC (524 bp) of pediocin PA-1 and the bacteriocins are considered similar to pediocin PA-1.